Kekerasan negara menular ke masyarakat - Rieke, 1974- (Yogyakarta : Galang Press, 2004)
Social violence as a result of state violence during the New Order government in Indonesia
Includes bibliographical references (p. 201-208).
Keywords: Indonesia -- Politics and government